Bradykinin-Mediated Angioedema: An Update of the Genetic Causes and the Impact of Genomics - Marcelino-Rodriguez, Itahisa; Callero, Ariel; Mendoza-Alvarez, Alejandro; Perez-Rodriguez, Eva; Barrios-Recio, Javier; Garcia-Robaina, Jose C.; Flores, Carlos (Frontiers in Genetics, 2019)
Recurrent episodes of bradykinin-mediated angioedema (Bk-AE) can associate with acquired or hereditary conditions, the former most commonly developing secondarily to a pharmacological treatment. Despite successful genomic advances that have led to the identification of a large number of disease genes irrespective of disease prevalence, their application to Bk-AE has barely occurred. As a consequence, the genetic causes of Bk-AE remain poorly understood, obstructing the identification of patient subtypes and the development of precision medicine strategies. This review provides an update of the genetic studies completed to date on the acquired forms, which have almost exclusively focused on Bk-AE secondarily to the angiotensin-converting enzyme inhibitor treatment, and the blooming subdivision of the hereditary forms established by the identification of novel causal genes with next-generation sequencing (NGS) technology-based exome studies in genetically undiagnosed patients. Finally, based on the diverse benefits that are offered by the technology, we present arguments favoring the use of holistic NGS approaches as first-tier genetic tests as a promise to reduce the diagnostic odyssey of patients with suspected hereditary forms of Bk-AE.